ADAPTIVE ESTIMATION ALGORITHMS FOR THE STATE OF NONLINEAR DYNAMIC SYSTEMS - Zaripov, O.O.; Akhmedov, D.A.; Mamirov, U.F. (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the construction of adaptive state estimation algorithms for nonlinear dynamic systems. The tasks of adaptive state estimation, adaptive identification of parameters, and constructing an adaptive observer are considered. The conditions of global stability of an adaptive observer are given. The above algorithms for adaptive state estimation, adaptive parameter identification, and the construction of an adaptive observer of a nonlinear dynamic system make it possible to increase the accuracy of estimating the state vector and thereby the quality indicators of control processes.